THE EFFECTIVENESS OF THE IMPLEMENTATION PQ4R METHOD TO STUDENTS’ READING COMPREHENSION ELABORATED IN YOUTUBE - Putri, Tri Cantika; Bunau, Eusabinus; Salam, Urai; Yuliana, Yohanes Gatot Sutapa; Rosnija, Eni (STKIP Persada Khatulistiwa Sintang, 2024)
The role to teach reading of recount text material for junior high school is perceived unattractive and ineffective. The purpose of this current study was to figure out the effectiveness of the implementation Preview, Question, Read, Reflect, Recite, Review (PQ4R) Method to teach students' reading comprehension on YouTube. Using simple random sampling technique, 33 students were selected from VIII C grade students of SMPN 01 Siantan in academic year 2022/2023. The data analysis method of this study was pre-experimental research with pre-test and post-test one group design model which the experiment carried out only in one group without comparison group. The result of this study revealed that before treatment was given, the students’ mean score was 51.97, while in contrast, the mean score of after treatment was 80.76. In data analysis, the result of the effect size computation was 1.88 which was indicated as strong effect. It can be recommended that junior high school teachers to implement PQ4R learning method to enhance students’ reading comprehension.